Verbal Phatic Expressions in EFL Student Teachers' Classroom Interaction - Alek Alek; Van Tuyen Nguyen (Naifaderu Cipta Sejahtera, 2023)
Purpose The present study explores the types and utilization of verbal phatic expressions used by student teachers of English as a Foreign Language (EFL) during classroom interactions. This teaching strategy is perceived as being crucial for communicative EFL teaching especially in high-context cultures. Methodology The present study adopted a qualitative approach utilizing a descriptive research design to address the research inquiries. The data collection process involved a series of observations and semi-structured interviews, with a cohort of seven participants. Results/Findings The findings indicate the existence of twelve types of phatic expressions observed in the study. These encompass greetings, small talk, compliments, apologies, expressions of gratitude, farewells, polite phrases, affirmative expressions, negative responses, interjections, hedges, and filler words. Meanwhile, an examination of the data revealed that among the various phatic expressions employed by EFL student teachers in the context of classroom interaction, ten of them were found to be the most frequently utilized. These include greetings, small talk, compliments, apologies, expressions of gratitude, farewells, polite phrases, affirmative expressions, hedges, and filler words. The utilization of these expressions by student teachers served the purpose of facilitating a seamless continuity of interaction within the classroom. Implications This qualitative study presents pedagogical implications that are relevant to both EFL teachers and students, as it highlights the significance of exposure to both language competence and performance in the educational setting.